Quench Pool Boiling with Temporary Crystalline Enhancers. Issue 2 (8th January 2014) - Ladizhensky, Izhak; Korin, Eli; Mazor, Gedalia; Nemirovsky, Dmitry; Goldkin, Evgeny
Abstract In some industrial activities, the use of permanent heat transfer enhancements such as metal coating, pins, and grooves in cryogenic treatment is quite problematic. Such permanent heat transfer enhancers were replaced with temporary enhancers made of different crystalline materials, here focusing on NaCl, MgSO4·7H2O, CaCl2·2H2O, and C6H5Na3O7·2H2O, which were used during quenching of the sample in the cryogenic liquid, i.e., nitrogen. The time required for sample cooling until the liquid nitrogen saturation temperature is reached decreases significantly when a crystalline coating is applied. The dependence of the cooling time on temporary coating creation parameters such as solution concentration, initial temperature of the sample, and solution spreading time is discussed.